GLOBAL VALUE CHAIN PARTICIPATION OF AN INDONESIAN MODEST FASHION SME’s: A CASE STUDY FROM MALANG - Setyawati, Dyah; Sudarmiatin, Sudarmiatin; Pratikto, Heri (Universitas Nusa Cendana, 2026)
This study examines the participation of an Indonesian modest fashion SME in the global value chain. The research focuses on an Abaya-producing SME in Malang that has expanded its market to several international destinations. Data were collected through in-depth interviews, observation, and supporting documentation, and analyzed thematically. The findings show that the firm entered export markets gradually through digital platforms, exhibitions, and direct communication with overseas buyers. Its global value chain participation was strengthened by trust-based relationships, product adaptation, quality control, and continuous learning in export procedures. The study also finds that internationalization encouraged capability upgrading and created local economic benefits through the involvement of community-based workers. This case suggests that SME participation in global value chains can develop incrementally through adaptive learning, relational governance, and strong local production linkages. Keywords : Global Value Chain; Modest Fashion; SME Internationalization;Uppsala Model